2005
DOI: 10.1016/j.febslet.2005.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfoxide as an inducer of differentiation in preosteoblast MC3T3‐E1 cells

Abstract: Osteoblastic differentiation is an essential part of bone formation. Dimethyl sulfoxide (DMSO) is a water miscible solvent that is used extensively for receptor ligands in osteoblast studies. However, little is known about its effects on osteoblastogenic precursor cells. In this study, we have used a murine preosteoblast cell line MC3T3-E1 cells to demonstrate that DMSO effectively induces osteoblastic differentiation of MC3T3-E1 cells via the activation of Runx2 and osterix and is dependent upon the protein k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…It seems likely that DMSO-treated cells achieved a heightened state of differentiation reflected by an enhanced capacity to mineralize the surrounding extracellular matrix. Cheung et al (12) examined Runx2 and osterix induction by DMSO in normal ␣-MEM at 5 days only; Runx2 (1.89-fold) and osterix (1.39-fold) induction by DMSO was significant. In contrast, we examined the effect of DMSO on target gene expression using a number of target genes at numerous time points in OM; in particular, we observed strong induction of osterix by DMSO over the entire time period of mineralization, including days 3 and 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems likely that DMSO-treated cells achieved a heightened state of differentiation reflected by an enhanced capacity to mineralize the surrounding extracellular matrix. Cheung et al (12) examined Runx2 and osterix induction by DMSO in normal ␣-MEM at 5 days only; Runx2 (1.89-fold) and osterix (1.39-fold) induction by DMSO was significant. In contrast, we examined the effect of DMSO on target gene expression using a number of target genes at numerous time points in OM; in particular, we observed strong induction of osterix by DMSO over the entire time period of mineralization, including days 3 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, DMSO is used as a cryo-preserving agent in cell banking (11) commonly at 10% concentrations that are then injected directly into the patient. Notably, DMSO is reported to stimulate osteoblast differentiation in MC3T3-E1, a mouse pre-osteoblast cell line, through ERK activation of transcription factors Runx2 and osterix (12).…”
mentioning
confidence: 99%
“…Protein kinase C (PKC) and/or PKD have been known to be associated with osteoblastic differentiation (18)(19)(20). To investigate whether PKC or PKD mediate the Rh2(S)-induced differentiation and mineralization of osteoblastic MC3T3-E1 cells, two different staurosporine-derived inhibitors were utilized: Go6983 for PKCα, βI, βII, δ and γ and Go6976 for PKCα, βI and PKCµ/PKD.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed negative role of PKCμ in osteogenesis is in contrast to what has been reported previously, where PKCμ was shown to be involved in activating MC3T3 osteogenic differentiation [144,145]. Furthermore, Cecil and colleagues concluded that PKCμ is implicated in BMP-2 and IGF-I induced RUNX2 activity in hMSCs and mineralization using a 10µM dose of Gö6976 to demonstrate this [146].…”
Section: Discussionmentioning
confidence: 92%
“…Some reports show that certain PKC isozymes are involved in osteogenic differentiation or osteoblast proliferation. For instance, PKCδ and PKCμ, are known to be involved in osteogenic differentiation in murine cells and animal models and PKCα has been implicated in human osteoblasts proliferation [98,100,144]. We treated hMSCs with PKC activators and inhibitors to investigate cell proliferation and differentiation in vitro, and observed that different PKC subfamilies had opposite roles in ALP expression and mineralization.…”
Section: Improving Hmsc Osteogenic Differentiationmentioning
confidence: 99%